Bridge to Terabithia [videorecording (DVD)] - Csupo, Gabor; Hutcherson, Josh; Robb, AnnaSophia, 1993-; Patrick, Robert, 1958-; Paterson, Katherine (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
Jesse Aarons is in the 5th grade and has trained all summer to become the fastest runner in school. He becomes upset when new classmate Leslie Burke outruns him and everyone else. Despite this and some other striking differences, the two become fast friends. Together, they create Terabithia where they rule as king and queen and is a land filled with monsters, trolls, ogres, and giants. This friendship helps Jesse cope with a tragedy that makes him realize what Leslie taught him.